Novel Pattern of Iron Deposition in the Fascicula Nigrale in Patients with Parkinson’s Disease: A Pilot Study - Miriam E. Peckham; Khashayar Dashtipour; Barbara A. Holshouser; Camellia Kani; Alex Boscanin; Kayvan Kani; Sheri L. Harder (Radiology Research and Practice)
Background and Purpose. To determine whether the pattern of iron deposition in the fascicula nigrale in patients with Parkinson’s disease would be different from age-matched controls by utilizing quantitative susceptibility mapping to measure susceptibility change. Methods. MRIs of the brain were obtained from 34 subjects, 18 with Parkinson’s disease and 16 age- and gender-matched controls. Regions of interest were drawn around the fascicula nigrale and substantia nigra using SWI mapping software by blinded investigators. Statistical analyses were performed to determine susceptibility patterns of both of these regions. Results. Measurements showed significantly increased susceptibility in the substantia nigra in Parkinson’s patients and an increased rostral-caudal deposition of iron in the fascicula nigrale in all subjects. This trend was exaggerated with significant correlation noted with increasing age in the Parkinson group. Conclusion. The pattern of an exaggerated iron deposition gradient of the fascicula nigrale in the Parkinson group could represent underlying tract dysfunction. Significant correlation of increasing iron deposition with increasing age may be a cumulative effect, possibly related to disease duration.